2018
DOI: 10.18632/oncotarget.26349
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing reveals recurrence-associated genomic alterations in early-stage non-small cell lung cancer

Abstract: PurposeThe identification of genomic alterations related to recurrence in early-stage non-small cell lung cancer (NSCLC) patients may help better stratify high-risk individuals and guide treatment strategies. This study aimed to identify the molecular biomarkers of recurrence in early-stage NSCLC.ResultsOf the 42 tumors evaluable for genomic alterations, TP53 and EGFR were the most frequent alterations with population frequency 52.4% and 50.0%, respectively. Fusion genes were detected in four patients, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…MUC16 is overexpressed in several cancers including ovarian, pancreatic, breast, and lung, and has been shown to be associated with cancer progression and poor prognosis 64 . SMARCA4, also frequently mutated in recurrent tumors in our study, has been previously shown to be associated with recurrence in lung adenocarcinoma 32,33 . SMARCA4 is a DNA-dependent ATPase which is involved in transcription regulation via the SWI/SNF chromatin remodeling complex 65 .…”
Section: Discussionsupporting
confidence: 71%
“…MUC16 is overexpressed in several cancers including ovarian, pancreatic, breast, and lung, and has been shown to be associated with cancer progression and poor prognosis 64 . SMARCA4, also frequently mutated in recurrent tumors in our study, has been previously shown to be associated with recurrence in lung adenocarcinoma 32,33 . SMARCA4 is a DNA-dependent ATPase which is involved in transcription regulation via the SWI/SNF chromatin remodeling complex 65 .…”
Section: Discussionsupporting
confidence: 71%
“…The unknown genetic alterations, RNA editing factors mutations, transcription factor mutations, or epigenetic alterations, except known driver mutations, might cause recurrence in the tumors without alteration. 11 The number of mutations in the targeted NGS did not seem to be affected by clinical factors such as age or smoking history. However, previous whole gene or whole exon sequencing studies showed an association with the number of mutations and clinical factors.…”
Section: Discussionmentioning
confidence: 90%
“…However, 230 patients is not a small number for an NGS study focused only on early lung adenocarcinoma, compared with previous NGS studies. 11,27 The CTNNB1 and fusion genes were rare, and the recurrence rate of early lung cancer was low, so the number of patients with recurrencerelated specific genes was inevitably small. However, these genes showed strong correlations with recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS patients with lung cancer respond poorly to immune checkpoint inhibitors compared to ES 9 . It has been suggested that tumour cell intrinsic factors such as lower TMB (and presumably lower neoantigen load) and lower expression of PDL1 account for this reduced sensitivity 10,11,12 . Yet, even in a cohort selected for high expression of PDL1, NS LUAD patients had worse progression free survival and less durable responses to anti-PD(L)1 therapy than heavy smokers 13 .…”
Section: Introductionmentioning
confidence: 99%